The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
Engineering for Rural Development 2019
DOI: 10.22616/erdev2019.18.n198
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tillage methods on optimization of nutrition, yield and filling grain of winter wheat on leached chernozem

Abstract: Based on the conducted research, experimental data were obtained that allowed recommending a calculation and balance method for determining fertilizer rates for constructing a fertilizer calculation system, which allowed obtaining the maximum yield of winter wheat (6.01 t•ha-1) after the forecrop peas on leached chernozem. The optimal combination of systems for fertilizing winter wheat after its forecrop peas with methods and techniques for placing mineral fertilizer in a 0-20 cm soil layer has been establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…In addition, the elements that make up fertilizers can directly inhibit the development of fungal pathogens (Golosnoy et al, 2019;Właśniewski et al, 2019). To obtain a high yield of winter wheat, it is necessary to strictly control the amount of applied mineral fertilizers (Al-Saidan et al, 2019;Grechishkina et al, 2019;Korostylev et al, 2019).…”
Section: Problem Statementmentioning
confidence: 99%
“…In addition, the elements that make up fertilizers can directly inhibit the development of fungal pathogens (Golosnoy et al, 2019;Właśniewski et al, 2019). To obtain a high yield of winter wheat, it is necessary to strictly control the amount of applied mineral fertilizers (Al-Saidan et al, 2019;Grechishkina et al, 2019;Korostylev et al, 2019).…”
Section: Problem Statementmentioning
confidence: 99%
“…Modern cultivation of winter wheat is aimed at intensification of its technology, so ensuring reliable and long-term protection against diseases is very important [1,2,3,4]. The following diseases are of great economic importance in cereals: ear Fusarium, Septoriosis, powdery mildew, pyrenophorosis, brown rust, which damage both the quality and quantity of the growing crop [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Leading scientists from many countries are engaged in the development and improvement of tillage machines with rotary working tools [2][3][4][5][6]. Having studied the research in this area, we revealed that the use of rotary working tools is a promising direction in the development of new machines for tillage [7][8][9][10]. Their main advantage, in comparison with passive working tools, is that they are less energy-intensive.…”
Section: Introductionmentioning
confidence: 99%